Dispute Resolution Between Transportation Carrier/Freight Forwarder Services and Exporters Regarding Damage to Goods/Cargo by Sea Line in Medan - Audrey, Fiona; Pakpahan, Kartina; Rizal, Said (IJBLE Scientific Publications Community Inc., 2024)
Sea transportation services that transport certain goods have many problems, for example related to the responsibility of sea transportation services for damage to goods or delays in goods, so these matters must be resolved in forums or dispute resolution institutions. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research, which is a method that functions to describe or provide an overview of the object under study. The data source used is secondary data with quantitative data analysis. The results of this research are that the carrier must be responsible if loss or damage occurs from the transportation activity. As explained in Article 40 to Article 42 of the Shipping Law, the carrier company is responsible for the safety of the goods or passengers it transports in accordance with the agreement agreed upon by both parties.